The Mountain verbal courts of the Kuban and Tersk oblasts (1871–1918): the main directions and prospects of comparative historical research - Mirbek Aslanovich Hagazheev (Кавказология, 2023)
The article considers the main directions and prospects of comparative historical research of the activities of the mountain verbal courts of the Kuban and Tersk regions in 1871-1917.It is noted that the specifics of their activities were determined to a certain extent by the peculiarities of their territorial jurisdiction.In this regard, the extraterritorial principle of their activities is characterized, when their territorial jurisdiction coincided with the ethnic territory of a particular people and sometimes went beyond the boundaries of the political and legal entity within which they were created and functioned.It has been established that the main directions of comparative historical research of their activities may be related to the study of the features of their territorial organization and the identification of local features of functioning, analysis of the range of disputes and conflicts under consideration (murders, injuries, theft, property and inheritance disputes) and other issues they resolve (related to the establishment of guardianship and guardianship, religion) and etc. Attention is drawn to the interaction of the mountain verbal courts with government institutions, institutions of self-government and people's justice (mediation/mediation courts).It is concluded that a comparative historical study of the activities of these institutions will significantly expand the understanding of them as an important mechanism for the incorporation of the indigenous peoples of the Kuban and Tersk regions into the political and legal space of Russia.